Information on Online Promotion Strategies Based on Go-Food Applications in Creating Marketing Effectiveness - Hermiyetti, Hermiyetti; Dewi, Luh Komang Candra; Dharmawan, Donny; Junaedi, I Wayan Junaedi; Utami, Eva Yuniarti (Universitas Dharma Wacana, 2023)
The research aims to explore the effectiveness of online promotion strategies through the Go-Food application for culinary MSMEs in Jakarta. This research explores the benefits and disadvantages of using online promotional strategies through the Go-Food application. Effectiveness is measured by the number of advantages obtained compared to the losses experienced. The research method is a case study with a qualitative approach. Data collection techniques were carried out using interviews, observation, documentation and literature study. The number of informants studied was 5 informants. The research results show that the online promotion strategy through the Go-Food application has benefits: increasing the number of consumers, expanding the market, increasing income, as a promotional medium, time efficiency and increasing credibility, while the disadvantages can be overcome by technological development carried out in the Go-Food application. Thus, the advantages of using an online promotion strategy through the Go-Food application outweigh the disadvantages, so it can be concluded that the online promotion strategy through the Go-Food application is effective for culinary MSMEs.